Case report: Discovery of novel CTNNB1 mutations and comparison of clinical characteristics in two patients with NEDSDV - Lee, Eojin; Choi, Ja Young; Yang, Shin-Seung (Frontiers in Genetics, 2025)
CTNNB1, which encodes β-catenin, plays an essential role in the Wnt signaling pathway and regulates cellular homeostasis. Mutations in this gene can lead to neurodevelopmental disorder with spastic diplegia and visual defects (NEDSDV). This study aimed to identify CTNNB1 mutations in two patients presenting with global developmental delay and compare their distinct phenotypes. Next-generation sequencing (NGS) was performed to detect mutations in CTNNB1. Longitudinal clinical observations were conducted to analyze the clinical features of the patients. The first patient was a 7-year-old boy who exhibited symptoms of microcephaly, spasticity, severe amblyopia with retinal detachment, and developmental delay. NGS identified a novel c.1170dupT, p. Ala391CysfsTer4 frameshift variant in CTNNB1. The second patient, a 8-year-old girl, had a dysmorphic face, severe global developmental delay, and ataxic gait. NGS revealed a c.1759C > T, p. Arg587Ter nonsense mutation in CTNNB1. Both patients shared common NEDSDV features; however, distinct phenotypic variations were observed depending on the type of genomic variant. NGS is crucial for the diagnosis of global developmental delay, particularly when brain magnetic resonance imaging (MRI) results appear normal. The identified novel frameshift variant expands the mutational spectrum of CTNNB1.